Circulating inflamma-miRs in aging and age-related diseases - Olivieri, Fabiola; Rippo, Maria Rita; Procopio, Antonio Domenico; Fazioli, Francesca (Frontiers in Genetics, 2013)
Evidence on circulating microRNAs (miRNAs) is indisputably opening a new era in systemic and tissue-specific biomarker research, highlighting new inter-cellular and inter-organ communication mechanisms. Circulating miRNAs might be active messengers eliciting a systemic response as well as non-specific “by-products” of cell activity and even of cell death; in either case they have the potential to be clinically relevant biomarkers for a number of physiopathological processes, including inflammatory responses and inflammation-related conditions. A large amount of evidence indicates that miRNAs can exert two opposite roles, activating as well as inhibiting inflammatory pathways. The inhibitory action probably relates to the need for activating anti-inflammatory mechanisms to counter potent proinflammatory signals, like the nuclear factor kappaB (NF-κB) pathway, to prevent cell and tissue destruction. MiRNA-based anti-inflammatory mechanisms may acquire a crucial role during aging, where a chronic, low-level proinflammatory status is likely sustained by the cell senescence secretome and by progressive activation of immune cells over time. This process entails age-related changes, especially in extremely old age, in those circulating miRNAs that are capable of modulating the inflammatory status (inflamma-miRs). Interestingly, a number of such circulating miRNAs seem to be promising biomarkers for the major age-related diseases that share a common chronic, low-level proinflammatory status, such as cardiovascular disease (CVD), type 2 diabetes mellitus (T2DM), Alzheimer Disease (AD), rheumatoid arthritis (RA), and cancers.